Structural and health functionality of dried goji berries as affected by coupled dewaxing pre-treatment and hybrid drying methods. Issue 1 (1st January 2018) - Song, Huihui; Bi, Jinfeng; Chen, Qinqin; Zhou, Mo; Wu, Xinye; Song, Jianxin
ABSTRACT: Coupled effects of sodium carbonate (SC) pre-treatment and hybrid drying methods (freeze-drying (FD)-instant controlled pressure drop drying (DIC), hot air drying (HAD)-DIC) on the microstructure, physicochemical, nutritional, and antioxidant properties of goji berries were investigated. Dewaxing pre-treatment by SC could decrease drying time and improve quality. A substantial increase in pore size of goji was found after SC pre-treatment coupled with hybrid drying. Although the best colour was found in FD products, goji dried by hybrid methods (especially FD-DIC) showed better overall quality than that dried by HAD or FD alone. FD-DIC products exhibited the lowest moisture content (127 g/kg), the best crispness (21), the highest glass transition temperature (27.82ºC), higher contents of total Lycium barbarum polysaccharide (139.8 g/kg), total carotenoids (2.43 g/kg) as well as ABTS + radical scavenging activity (57.55 μmol TE/g). FD-DIC could be an alternative drying method for processing valuable agro-products.